Multicural Awareness Among Millenial and Gen Z Teacher in Multicultural Education - Aisyah Khoirunnisa; Nandang Budiman; Sardin (al-Afkar, Journal For Islamic Studies, 2025)
Multicultural awareness can be the first step, especially for teachers to form a more tolerant and empathetic generation in multicultural education. This study explores multicultural awareness between millennial teachers and gen z teachers in Indonesia. This study uses a quantitative approach by collecting data using the Teacher Multicultural Attitude Survey (TMAS) instrument. The sample of this study is 140 from various schools in Indonesia. The results of the study showed that there was no significant difference in multicultural awareness between millennial teachers and gen z teachers. Reflecting that the generation factor is not a barrier for teachers in realizing multicultural awareness. This research also suggests the supervision and development of teacher multicultural awareness that is continuous and uniform in each generation. Further research can be more in-depth to examine multicultural awareness with other variables such as student learning outcomes or inclusive competencies